Tipo de luz en la captura de flebotominos (Diptera: Psychodidae) - Jeraldo, Verônica de Lourdes Sierpe; Casanova, Claudio; De Araújo, Edilson Divino; Cruz, Danilo Esdras Rocha; Pinto, Mara Cristina [UNESP]; De Melo, Claudia Moura (My University, 2012)
The number of visceral leishmaniasis cases has been gradually increasing in Brazil. One of the strategies to reduce the disease transmission is based on vector control. It is therefore of great epidemiological importance to develop more refined methods for monitoring and controlling its vectors, which are the phlebotomine sand flies. The present study evaluates the performance of traps using UV light or conventional incandescent, or white, light in sand flies captures. Traps baited with UV light caught higher numbers of sand flies than traps baited with white light, indicating the potential use of UV light, especially in locations of low sand flies densities.
Type of light in sand fly captures (Diptera:Psychodidae)
Keywords: Lutzomyia longipalpis; Sand flies; UV light